(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The editorial aims to introduce Teacher’s World: Journal of Education and Research (TWJER) Volume 49 (1) and highlight its contribution to nurturing knowledge for the Bangladesh education system. The upcoming issue focuses on the ever-evolving landscape of education in the 21st century, emphasizing the significance of knowledge in education. Twelve original research articles are set to be published, covering diverse topics such as teachers’ attitudes towards ICT integration, factors affecting accessibility for children with disabilities, sex education, TPCK, student participation, motivation, Facebook use, professional development, and global citizenship education. The articles are organized chronologically according to education levels—primary, secondary, and tertiary. The issue underscores the critical role of cultivating knowledge amid rapid advancements and employs various approaches and methodologies, including innovative pedagogical practices and technology integration. TWJER serves as a platform for dialogue and collaboration, encouraging reflection on adapting methodologies to diverse learner needs, the role of technology, and ensuring equitable access to quality education. The editorial anticipates that the shared knowledge will inspire actionable changes in classrooms, institutions, and educational policies. It positions the issue not just as an academic repository but as a catalyst for change, aiming to present research that not only analyzes the current state of education but also envisions possibilities for growth and improvement. Teacher’s World: Journal of Education and Research, 49 (1), 1-17